Length-Preserving Intramedullary Femoral Fixation for Traumatic Leg Amputation: A Case Report. Issue 2 (April 2015) - Bauer, Jennifer M.; Callan, Alexandra K.; Jahangir, A. Alex
Abstract : Case: We present the case of a twenty-one-year-old woman with a traumatic left leg amputation, substantial proximal skin degloving, and an ipsilateral femoral fracture treated with revision amputation distal to the fracture site and retrograde femoral nailing through the amputation site. Conclusion: A short retrograde femoral nail is a surgical option to fix a femoral shaft fracture proximal to a traumatic amputation in order to preserve limb length for effective prosthetic fit and ambulation.